Dual Posteromedial Portal Technique for Surgical Repair of an Unstable Medial Meniscal Ramp Lesion - Joshua S. Green MS; Sercan Yalcin MD; Jay Moran BS; William M. McLaughlin MD; Michael J. Medvecky MD (SAGE Publishing, 2022)
Background: Medial meniscal ramp lesions, which commonly occur in the setting of anterior cruciate ligament (ACL) ruptures, are defined as structural lesions at the medial meniscocapsular junction and can involve the posteromedial capsular attachments or most peripheral aspect of the meniscus. Unstable ramp lesions can lead to rotational instability within the knee and may play a role in ACL graft failure if left untreated. The novel use of dual posteromedial portals, similar to those used in an arthroscopic labral repair, may allow for enhanced visualization, optimal access to the posteromedial compartment, and easier manipulation of the instrumentation for successful surgical repair of hidden ramp lesions. Indications: Surgical repair of medial meniscal ramp lesions is indicated in patients with a clinically unstable meniscus when probed during arthroscopy. Technique Description: This surgical technique video demonstrates a dual posteromedial portal arthroscopic approach to repair an unstable medial meniscal ramp lesion using a case example from a patient with a concomitant ACL rupture. Results: Surgical repair of medial meniscal ramp lesions has been reported to show improvements in meniscus healing and knee stability. Discussion/Conclusion: The use of dual posteromedial portals offers improved accessibility to the posteromedial compartment of the knee and provides excellent visibility during the surgical repair of a medial meniscal ramp lesion. The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.